Croatian adult health survey : a tool for periodic cardiovascular risk factors surveillance - Vuletić, Silvije (Array, 2009)
Summary: National risk factors surveys present very important tool for gathering population based health related information for policy. Croatian Adult Health Survey (CAHS) is such a tool, intended to collect population-based, representative and authoritative information on cardiovascular risk factors prevalence. The CAHS sample was designed to provide nearly complete coverage (98%) of the Croatian adult population, based on the random selection of the adult member of the household that was selected in the complex sampling scheme. Additionally, seven-step weighting scheme was applied to the dataset, in order to further increase the representativeness of the sample which is consequently considered to be representative for six geographical and administrative regions of Croatia, while it is considered only to be informative for the county-based estimates. The first cycle of the project took place in 2003, with a total of 9,070 respondents. The second project cycle is taking place in 2008. It has now been converted into the follow-up study (re-surveying the 2003 sample) and is being further supplemented with additional questions, qualitative investigation module and an intervention performed by the public health nurses. The CAHS provides not only the basis for health information for policy, but also serves as a platform for a number of ongoing public health collaborations and a valuable public health research resource